Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

Microplastics favor forbs over grasses in drylands: Opposing roles of particulates and chemical leachates on germination and plant traits - Yudi M. Lozano; Leonie S. Kuhlmann; Julian W. Zeller; Alejandro Terrones; Cristina Armas (Plant and Soil, 2026)
Background and aims Drylands face increasing microplastic pollution. We tested how plastic particulates and leachable chemicals affect key dryland plants (grasses and forbs). Methods We performed two controlled experiments using dryland grasses and forbs, and evaluated the effect of plastic particulates and leachables on germination, plant morphological and physiological traits. Results Plastic particulates reduced grasses germination velocity by ~ 17% compared to soils without particulates, likely by trapping seeds and impairing water uptake. Most forbs were marginally affected, although germination was inhibited in mucilage-producing species. Notably, leachates stimulated forbs germination through hormesis, contrasting with particulates physical inhibition. For instance, E. vulgare velocity increased by ~ 20% with leachates than without them. However, this stimulation was transient and faded in later development. Grasses shoot mass decreased by ~ 21% with particulates, likely from soil water loss via plastic-induced cracks, an effect exacerbated by their shallow root systems. Forbs avoided this stress through deeper rooting and benefited from improved soil aeration, which enhanced shoot growth by ~ 61% compared to control. Grasses allocated carbon to stress tolerance, increasing photosynthetic rates (+ 15%) and water-use efficiency (+ 7.2%). Forbs favored shoot growth despite lower photosynthetis (-8.1%) and water-use efficiency (-25%), using thinner leaves and higher transpiration rates. Root morphology also critically influence tolerance to microplastics. The divergent particulate effects on grasses and forbs, reveal a mechanistic trade-off between stress tolerance and growth investment. Conclusion Microplastic particulates, more than leachates, drive plant responses, suggesting that plastic pollution may act as environmental filter by favoring stress-adapted forbs over grasses.

Influence of abiotic factors on the germination of an endemic sea lavender: First steps to shape local assemblage - Joaquín Moreno; Alejandro Terrones; Ana Juan (Estuarine, Coastal and Shelf Science, 2024)

An approach to quantitative plant–soil relationships of saltcedar woodlands throughout central and southeastern Iberian Peninsula (Spain) - Joaquín Moreno; Alejandro Terrones; María Ángeles Alonso; Ana Juan (European Journal of Forest Research, 2019)

Halophytic plant community patterns in Mediterranean saltmarshes: shedding light on the connection between abiotic factors and the distribution of halophytes - Joaquín Moreno; Alejandro Terrones; Ana Juan; María Ángeles Alonso (Plant and Soil, 2018)

Taxonomic status of Ononis tridentata (Fabaceae) from Morocco, resolved by multivariate morphometric analyses - Jonás C. Agulló; Ana Juan; MÁngeles Alonso; Alejandro Terrones; Manuel B. Crespo (Plant Biosystems, 2013)